2022
DOI: 10.1038/s12276-022-00773-5
|View full text |Cite
|
Sign up to set email alerts
|

Latrophilin-2 is a novel receptor of LRG1 that rescues vascular and neurological abnormalities and restores diabetic erectile function

Abstract: Diabetes mellitus (DM) is a chronic metabolic disorder characterized by inappropriate hyperglycemia, which causes endothelial dysfunction and peripheral neuropathy, ultimately leading to multiple complications. One prevalent complication is diabetic erectile dysfunction (ED), which is more severe and more resistant to treatment than nondiabetic ED. The serum glycoprotein leucine-rich ɑ-2-glycoprotein 1 (LRG1) is a modulator of TGF-β-mediated angiogenesis and has been proposed as a biomarker for a variety of di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 21 publications
(41 citation statements)
references
References 57 publications
0
35
0
Order By: Relevance
“…Twelve weeks after completing STZ injections (after induction), mice with a tail vein blood glucose level > 300 mg/dL and exhibiting a significant body weight reduction were considered to have DM. Fasting and postprandial blood glucose levels were determined using an Accu-Check blood glucose meter (Roche Diagnostics, Mannheim, Germany) [18].…”
Section: Animals and Treatmentsmentioning
confidence: 99%
“…Twelve weeks after completing STZ injections (after induction), mice with a tail vein blood glucose level > 300 mg/dL and exhibiting a significant body weight reduction were considered to have DM. Fasting and postprandial blood glucose levels were determined using an Accu-Check blood glucose meter (Roche Diagnostics, Mannheim, Germany) [18].…”
Section: Animals and Treatmentsmentioning
confidence: 99%
“…Recombinant human LRG1 protein and human LPHN2 variants protein (Lec, Olf, Lec/Olf domain, or ectodomain full) were expressed and puri ed as described previously 20 . LRG1 N-glycan mutants (N79D, N186D, N269D, and N325D) were constructed using the QuikChange Lightning Site-Directed Mutagenesis kit (#210518, Agilent Technologies) with the LRG1-Fc construct as a template.…”
Section: Recombinant Protein Expression and Puri Cationmentioning
confidence: 99%
“…Recently, we reported that adhesion GPCR latrophilin-2 (LPHN2) is a TGF-β-independent receptor of LRG1, and the LRG1/LPHN2 axis exerts both angiogenic and neurotrophic effects under hyperglycemic conditions 20 . Given that the secreted LRG1 can be differently glycosylated and alterations in sugar chains may in uence the function of LRG1 in cancer 41,42 , we questioned the functional signi cance of LRG1's Nglycans on the LRG1/LPHN2 axis.…”
Section: De-glycosylation Of Lrg1 Enhances the Binding A Nity Towards...mentioning
confidence: 99%
See 2 more Smart Citations